Quality traits and lipid composition of meat from Nellore young bulls fed with different oils either protected or unprotected from rumen degradation - Oliveira, E. A. [UNESP] (2012)
The qualitative characteristics, lipids and chemical composition of the meat of 35 Nellore young bulls were analyzed. These bulls had an average slaughter weight and fat thickness of 532.17 +/- 30.2 kg, and 7.00 mm, respectively. Significant differences were found only in the meat's water holding capacity (WHC), which was higher for animals fed with fresh linseed oil. More conjugated linoleic acid (CLA) was found in the meat of animals fed with unprotected soybean oil, while better omega-6/omega-3 ratios were noted for those fed unprotected linseed oil. The addition of different vegetable oils to the bulls' diet (soybean or linseed, either protected or not protected from rumen digestion) did not interfere with the qualitative characteristics of their meat while improving the lipid composition of the longissimus muscle. of the oils examined, unprotected linseed oil most improved the omega-6/omega-3 ratio, thus producing the healthiest meat for human consumption. (C) 2011 Elsevier Ltd. All rights reserved.